Contribution of Breastfeeding to False-Positive Saliva Polymerase Chain Reaction for Newborn Congenital Cytomegalovirus Screening. (1st February 2018) - Ross, Shannon A; Michaels, Marian G; Ahmed, Amina; Palmer, April L; Sánchez, Pablo J; Bernstein, David I; Feja, Kristina; Stewart, Audra; Boppana, Suresh B; Fowler, Karen B
Abstract : Saliva cytomegalovirus (CMV) polymerase chain reaction for newborn screening is highly sensitive. This study uses nationally published CMV seroprevalence and breastfeeding rates to demonstrate false-positive rates are unlikely to be significantly influenced by breastfeeding or other perinatal exposures. Abstract: Real-time polymerase chain reaction (PCR) of saliva is highly sensitive for newborn congenital cytomegalovirus (CMV) screening. This study uses nationally published CMV seroprevalence and breastfeeding rates to estimate the contribution of CMV DNA in breast milk to false-positive saliva PCR results. The false-positive rates adjusted for breastfeeding ranged from 0.03% in white Hispanic persons to 0.14% in white non-Hispanic persons. Saliva CMV PCR for newborn screening is highly sensitive, and the low false-positive rates in this study suggest that saliva PCR results are unlikely to be significantly influenced by breastfeeding or other perinatal exposures.